Manakah yang Lebih Diminati Masyarakat?: Bukalapak, Tokopedia atau Shopee - Dhani Wahyu Wijaya; Aji Prasetya Wibawa (Faculty of Economics and Business Universitas Jenderal Soedirman, 2020)
One of the drivers of technological advances is the Internet, which led to the occurrence of shifting trading patterns from offline to online. But the problem is that some users of e-marketplace services, such as Bukalapak, Tokopedia, and Shopee do not know what is most interested by the community. Therefore we need to do the research which one is most interested by the community. In this research conducted observations and analyses of Website features, featured Website features, promotions what is done and by using Google Trend, in a way by comparing the three e-marketplace. The results of this study are used to find out which people are most interested in and for reference in choosing e-marketplace for the perpetrators of small and medium enterprises (SMES) or the public.